The influence of radiotherapy on cardiac disorders - Ziółkowska, Ewa; Woźniak-Wiśniewska, Anita; Wiśniewski, Tomasz; Makarewicz, Roman; Sinkiewicz, Władysław (Contemporary Oncology/Współczesna Onkologia, 2009)
Cardiological disturbances are one of the late complications of radiotherapy of the area of the chest and usually appear over 10 years after the end of treatment. It is an essential problem in patients with breast cancer or Hodgkin’s lymphoma due to long-term survival in this group. Described disturbances were located mostly in the pericardium and coronary vessels, but can also involve the myocardium, the conducting system or valves of the heart. During the use of older techniques of irradiation the percentage of cardiological complications after the treatment was significant. Nowadays the dose which the heart receives is significantly reduced, but radiation damage of the heart is still common. It could be connected with the use of new, more cardiotoxic agents during chemotherapy, or result from potential hypersensitivity of the endothelial cells to low radiation doses. The aim of the study is to review the accessible literature about cardiological complications after the use of ionizing radiation.